2018
DOI: 10.14569/ijacsa.2018.090966
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Support Vector Machine, Maximum Likelihood and Neural Network Classification on Multispectral Remote Sensing Data

Abstract: Land cover classification is an essential process in many remote sensing applications. Classification based on supervised methods have been preferred by many due to its practicality, accuracy and objectivity compared to unsupervised methods. Nevertheless, the performance of different supervised methods particularly for classifying land covers in Tropical regions such as Malaysia has not been evaluated thoroughly. The study reported in this paper aims to detect land cover changes using multispectral remote sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…8. It is obvious that these regions possess different brightness conditions due to the different spectral properties of the materials [24]. Graphs of MSE versus noise density were then plotted to investigate the relationship between them for red, green and blue channel and for each of the regions.…”
Section: Methodsmentioning
confidence: 99%
“…8. It is obvious that these regions possess different brightness conditions due to the different spectral properties of the materials [24]. Graphs of MSE versus noise density were then plotted to investigate the relationship between them for red, green and blue channel and for each of the regions.…”
Section: Methodsmentioning
confidence: 99%
“…ML classification was carried out using all 6 bands to produce 11 classes, which were coastal swamp forest, dry land forest, oil palm, rubber, cleared land, sediment plumes, water, coconut, bare land, urban and industry [9], [10], [11]. To carry out ML classification on the hazy scenes, we need training pixels within the hazy scene.…”
Section: B ML Classification On the Simulated Hazy Imagesmentioning
confidence: 99%
“…In addition, SVM determines the hyperplane by maximizing the distance among classes (maximum margin), so that it has high generalization for the testing dataset. Thus, it is better than ANN in which it searches for a hyperplane by principally minimizing its gradient and depending on the number of parameters used [5][6][7][8]. SVM classification works using the principle of Structural Risk Minimization (SRM) to enable it to produce good generalizations with hyperplane fields which can minimize the average error in managing training dataset [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies showed that classification with SVM can significantly increase the accuracy value as in the classification to recognize the texture of honey pollen images in which the SVM accuracy results were better than Multilayer Perceptron classification method, Minimum Distance Classifier, and K-Nearest Neighbor [8][9]. SVM classification was tested by two public databases of DNA micro array to classify tumors and non-tumors resulting in a classification accuracy value in which SVM was better than ANN [10].…”
Section: Introductionmentioning
confidence: 99%